2007
DOI: 10.1007/s10800-007-9370-9
|View full text |Cite
|
Sign up to set email alerts
|

Surface active state involvement in electrocatalytic reductions at copper in acid solution

Abstract: The electrocatalytic behaviour of copper in acid is dominated by a metastable state interfacial redox transition which occurs within the double layer region, at ca. À0.7 (±0.1) V (SMSE). The transition in question is apparently based on the presence of low coverage, redox active, copper surface clusters which function as active sites or mediators and thus facilitate electron transfer across the interface; copper in acid exhibits a remarkably high overpotential of ca. 1.2 V for oxygen reduction. The effect of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 34 publications
1
14
0
1
Order By: Relevance
“…Cu + ads or Cu + 2,ads , at the copper surface. Further evidence to support this assumption was obtained recently from a study of the electrocatalytic properties of copper in acid [36]. Other authors have reported [37,38] that UPD copper on gold (a metal of similar character with regard to surface properties as copper) is also cationic in character).…”
Section: Copper Deposition Onto Rutheniummentioning
confidence: 82%
“…Cu + ads or Cu + 2,ads , at the copper surface. Further evidence to support this assumption was obtained recently from a study of the electrocatalytic properties of copper in acid [36]. Other authors have reported [37,38] that UPD copper on gold (a metal of similar character with regard to surface properties as copper) is also cationic in character).…”
Section: Copper Deposition Onto Rutheniummentioning
confidence: 82%
“…À0.5 V. The positively shifted peak potential at the HRP-NPC electrode should be attributed to the improved electrocatalytic activity of NPC. As demonstrated elsewhere (Burke and Sharna, 2007;Dima et al, 2003;Pletcher and Poorabedi, 1979), Cu was one of the most effective metals to catalyze the reduction of nitrogen containing compounds (e.g. the conversion of -NO 2 to -NH 2 ).…”
Section: Electrochemical Activity Of the Npc-based Electrodementioning
confidence: 83%
“…As a metal, copper is much cheaper than gold. It has also been reported that copper has a good catalytic effect on the electrochemical reduction of some small molecules such as nitrate ions and organic nitrocompounds (Dima et al, 2003;Burke and Sharna, 2007). Therefore, the use of nanoporous copper (NPC) as a substitute for NPG for enzyme immobilization will be a good attempt.…”
Section: Introductionmentioning
confidence: 99%
“…However, so far this property has rarely been used for analytical applications. Recently, copper electrochemistry has been studied and summarized [35], which shows that a surface activated copper might play an important role in the electrocatalysis of organic compounds. This work deals with the fabrication a high precision and inexpensive analytical method for the electrocatalytic reduction of H 2 O 2 .…”
Section: Introductionmentioning
confidence: 99%